Systematic review: The formation of personal brand - Firmansyah, Robby (Sungging: Journal of Innovative, Cultural, Transdisciplinary Art and Kriya Discourse, 2024)
The rise of personal branding utilisation as a communication strategy within various contexts results in its concepts and elements heterogeneity. On the one hand, its popularity accelerates the development of knowledge regarding establishing a personal brand; on the other hand, it contributes to the variety of its concepts and elements that become dependent on its context. This article aims to illustrate the development of understanding toward establishing the personal brand based on its formative dimensions and also to draw a more general description from the heterogeneity of its elements. The systematic review method is used to identify, analyse, and synthesise the elements that play a role in establishing the personal brand based on the existing literature. Based on the identification and elimination process toward initial literature, twenty-one (N=21) pieces of literature were selected as relevant sources to describe the development of personal brand establishment elements. The results show that values, personalities, and expertise become the most commonly used elements in the internal dimension of personal brand establishment. Process dimensions include the process of reflection, communication, and evaluation. The external dimensions consist of the role of the third party and the setting where the personal branding activity takes place.